Meningkatkan Pemahaman Siswa tentang Konsep Globalisasi dan Sikap Cinta Tanah Air melalui Metode Diskusi pada Mata Pelajaran PKn Kelas VI di SDN Nagrak 02 Kecamatan Sukaraja Kabupaten Bogor - Toti Rostini (MODELING: Jurnal Program Studi PGMI, 2018)
This study aims to obtain empirical data on the application of discussion methods to improve students' understanding of the concept of globalization in learning of Civics class VI in the State Elementary School Nagrak 02 District Sukaraja Bogor Regency. This research uses classroom action research method with sample of 31 children. From the results of data analysis and understanding can be seen that the acquisition of research results increasing from cycle I to cycle II and to cycle III can achieve the indicator of success of the research that has been determined. The three indicators of research into the assessment of researchers is the activities of teachers, student activities and student test results. Application of discussion methods can improve students' understanding of the concept of globalization and can improve the love of homeland in the subjects of Civics class VI in SDN Nagrak 02 Kecamatan Sukaraja Kabupaten Bogor.